2010
DOI: 10.1371/journal.pone.0013122
|View full text |Cite
|
Sign up to set email alerts
|

Studies on a Novel Serine Protease of a ΔhapAΔprtV Vibrio cholerae O1 Strain and Its Role in Hemorrhagic Response in the Rabbit Ileal Loop Model

Abstract: BackgroundTwo well-characterized proteases secreted by Vibrio cholerae O1 strains are hemagglutinin protease (HAP) and V. cholerae protease (PrtV). The hapA and prtV knock out mutant, V. cholerae O1 strain CHA6.8ΔprtV, still retains residual protease activity. We initiated this study to characterize the protease present in CHA6.8ΔprtV strain and study its role in pathogenesis in rabbit ileal loop model (RIL).Methodology/Principal FindingsWe partially purified the residual protease secreted by strain CHA6.8Δprt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 41 publications
1
26
1
Order By: Relevance
“…These data indicated that all three proteases displayed enzymatic activities and were capable of hydrolyzing the synthetic peptide, albeit to different degrees. Consistent with our findings, during the preparation of this work, the enzymatic activity of VesC toward azocasein was reported (73). Next, to obtain further support for the suggestion that the Ves proteins are serine proteases, we examined the effects of AEBSF (serine protease inhibitor) and leupeptin (serine/cysteine protease inhibitor) on the proteolytic activity of VesA, VesB, and VesC.…”
Section: Cholerae Secretes a Variety Of Proteins In Rich Medium-supporting
confidence: 86%
See 1 more Smart Citation
“…These data indicated that all three proteases displayed enzymatic activities and were capable of hydrolyzing the synthetic peptide, albeit to different degrees. Consistent with our findings, during the preparation of this work, the enzymatic activity of VesC toward azocasein was reported (73). Next, to obtain further support for the suggestion that the Ves proteins are serine proteases, we examined the effects of AEBSF (serine protease inhibitor) and leupeptin (serine/cysteine protease inhibitor) on the proteolytic activity of VesA, VesB, and VesC.…”
Section: Cholerae Secretes a Variety Of Proteins In Rich Medium-supporting
confidence: 86%
“…5 and 6). However, a very recent study has shown that VesC induces a hemorrhagic response when injected into rabbit ileal loops suggesting that it may play a role in pathogenesis (73). As we have showed here; however, this activity does not seem to be required for intestinal colonization of mice.…”
Section: Discussioncontrasting
confidence: 43%
“…Initially ligated loops of rabbit small intestine were used as a model to assess the contribution of putative virulence factors to bacterial pathogen-induced diarrhea. This model was used for Vibrio cholerae, where the injection of whole cultures (24,25), culture supernatants (26), and cell extracts (27) caused dilation of the loop due to fluid accumulation. The rabbit ileal loop model also has been used to study pathogenesis of Escherichia coli (28)(29)(30), Salmonella (20,31,32), Shigella (33), Pseudomonas aeruginosa (34), Clostridium perfringens (35), Vibrio parahaemolyticus, Vibrio alcaligenes (36), and Bacillus cereus (37).…”
mentioning
confidence: 99%
“…In contrast, at high cell density (HCD), the intracellular HapR concentration is increased, leading to repression of the above-described processes and upregulation of expression of the hemagglutinin protease gene hapA, which codes for the major protease HAP of V. cholerae. Several reports indicate that HAP is most likely involved in V. cholerae's pathogenesis program (7,16,35,47), including its role in detaching adhered V. cholerae cells on intestinal epithelial cell surfaces.…”
mentioning
confidence: 99%